7x - 3y = 4
2x - 4y = 1
The solution to the system of equations is _____.
(13/34, -15/34),
(3/22, -7/22),
(13/22, 1/22).

7x - 3y = 4 multiple 4 on both sides; 28x - 12y = 16 (equation 1) 2x - 4y = 1 multiple 3 on both sides, 6x - 12y = 3 (equation 2) equation 1 - equation 2 the result is: 22x = 13, x = 13/22 7(13/22) - 3y = 4 (91/22) - 3y = 4 -3y = 4 - (91/22) = 88/22 - 91/22 = -3/22 y = (-3/22)/(-3) = 1/22 The solution for the system 7x - 3y = 4, 2x - 4y = 1 is (13/22, 1/22).

Question

Asked 6/13/2013 9:08:15 AM

Updated 5/27/2014 9:46:02 PM

1 Answer/Comment

Rating

3

7x - 3y = 4 multiple 4 on both sides;

28x - 12y = 16 (equation 1)

2x - 4y = 1 multiple 3 on both sides,

6x - 12y = 3 (equation 2)

equation 1 - equation 2 the result is:

22x = 13,

x = 13/22

7(13/22) - 3y = 4

(91/22) - 3y = 4

-3y = 4 - (91/22) = 88/22 - 91/22 = -3/22

y = (-3/22)/(-3) = 1/22

The solution for the system 7x - 3y = 4, 2x - 4y = 1 is (13/22, 1/22).

28x - 12y = 16 (equation 1)

2x - 4y = 1 multiple 3 on both sides,

6x - 12y = 3 (equation 2)

equation 1 - equation 2 the result is:

22x = 13,

x = 13/22

7(13/22) - 3y = 4

(91/22) - 3y = 4

-3y = 4 - (91/22) = 88/22 - 91/22 = -3/22

y = (-3/22)/(-3) = 1/22

The solution for the system 7x - 3y = 4, 2x - 4y = 1 is (13/22, 1/22).

Added 5/27/2014 9:46:02 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/27/2014 9:50:00 PM]

Solve (4 - x = -1) n (2 + 3x = 17). **Weegy:** 3(3x - 1) + 2(3 - x) = 0 9x - 3 + 6 - 2x = 0 9x - 2x + 3 = 0 7x = 0 - 3 7x = -3 x = -3/7 **User:** Solve (4 - x = -1) n (2 + 3x = 17). **Weegy:** hat depends on whether you mean (2/3)x or 2/(3x).
will do them both
For (2/3)x = 8, x = 8?(3/2) = 4?3 = 12
If you meant 2/(3x) = 8 then cross-multiply like this:
2 .... 8
- - = - -
3x ...1
2(1) = 8(3x)
2 = 24x so x = 2/24 = 1/12 (More)

Question

Not Answered

Updated 5/26/2014 11:34:32 PM

1 Answer/Comment

4 - x = -1

-x = -1 - 4

-x = -5

x = 5;

2 + 3x = 17

3x = 17 - 2

3x = 15

x = 5.

The solution for (4 - x = -1) n (2 + 3x = 17) is x = 5

-x = -1 - 4

-x = -5

x = 5;

2 + 3x = 17

3x = 17 - 2

3x = 15

x = 5.

The solution for (4 - x = -1) n (2 + 3x = 17) is x = 5

Added 5/26/2014 11:34:32 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/26/2014 11:36:01 PM]

The free-floating jellyfish structure is in ____ form?

Question

Expert Answered

Updated 8/11/2015 2:35:10 PM

1 Answer/Comment

The sum of the roots of 8x² - 2x = 1 **Weegy:** x= 3/2 (More)

Question

Expert Answered

Updated 8/12/2014 2:53:40 AM

1 Answer/Comment

27,356,614

questions answered

There are no comments.